EXCELLENT EMERGENCY NURSING CARE MANAGEMENT FOR MR. P WITH CHRONIC KIDNEY DISEASE IN ROOM RA 6, H. ADAM MALIK GENERAL HOSPITAL, NORTH SUMATERA PROVINCE, 2025 - Reja G Lumbantoruan; Siti Nurmawan; Eko Murdianto; Emma Angareni; Feronika Silalahi; Amelia Safira; Putri Sandiani Telaumbanua; Yanti, Lisda (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Chronic Kidney Disease (CKD) is a medical condition characterized by a gradual decline in kidney function over a period of at least three monts. This disorder causes the kidneys to become ineffective at filtering blood, leading to the accumulation of metabolic waste prodycts in the body. CKD is progressive and can lead to multisystem complications, especially in the end stages, which require renal replacement therapy such as hemodialysis. Some of the main risk factors for CKD include diabetes mellitus, hypertension, heart disease, and a family history of kidney disease. Globally, CKD is a non-communicable disease with high morbidity and mortality rates. In Indonesia, the prevalence of CKD increases annually, including at H. Adam Malik General Hospital, Medan. Based on medical records, in 2023, there were 619 hospitalizations and 184 cases in the adult ICU. Meanwhile, in 2024, there was an increase to 714 hospitalizations and 239 cases in the adult ICU. This data indicates a significant upward trend and is a concern in nursing services, particularly in emergency care.Based on this background, the author is interested in presenting a case study on service excellence-based emergency nursing care management for patients with CKD.